Stable and facile ethanol synthesis from syngas in one reactor by tandem combination CuZnAl-HZSM-5, modified-H-Mordenite with CuZnAl catalyst. (15th October 2019) - Cao, Zhikai; Hu, Tao; Guo, Jiawei; Xie, Jianrong; Zhang, Nuowei; Zheng, Jinbao; Che, Liming; Chen, Bing H.
Graphical abstract: Highlights: Ethanol is directly synthesized from syngas in one reactor. Successive modification HMOR with Zn and pyridine improves catalytic performance. Combination of CuZnAl-HZSM-5, modified-HMOR and CuZnAl catalyst exhibited a facile and stable ethanol synthesis. Abstract: A direct ethanol synthesis route from syngas in one reactor is achieved through tandem combination of CuZnAl-HZSM-5, H-Mordenite (HMOR) with CuZnAl catalyst. The HMOR zeolite plays a key role determining the whole catalytic performance. It is found that, among the studied HMOR, HOMR-20 (Si/Al = 20) exhibits the best catalytic performance. After an induction period (around 7 h), the CO conversion and ethanol selectivity reaches 6.4% and 50.1%. Modifying HOMR-20 with Zn can improve the catalytic performance. The initial CO conversion and ethanol selectivity is increased to 7.4% and 69.5%. However, Zn-HMOR-20 still suffers from deactivation. Modifying Zn-HMOR-20 with pyridine can further remarkably enhance the stability. After a long running time of 200 h, no deactivation is observed and CO conversion and ethanol selectivity are maintained at the values higher than 7.0 and 52.0%. Modifying with pyridine can effective inhibit carbon deposition over Zn-HMOR-20, which is mainly responsible for the excellent stability.